Telepharmacy -A Review - R. Margret Chandira (Journal of Global Pharma Technology, 2020)
It is fascinating to communicate that, the word Pharmacy is frequently animated up with alternative word Tele-pharmacy. In India, a pharmacist should be registered with state pharmacy council beforehand and then one can start working and inevitably one befits enumerated with pharmacy council of India when one is enumerated with all state pharmacy council, thus one can practice all over India.Telepharmacy is the use of telecommunications technology to provide pharmacist services to distant populations. Telepharmacy services may include drug review/monitoring, provision of drug information, medication dispensing, verification of oral and sterile compounding, patient assessment, patient counseling and medication therapy management To advance the circumstances is that a regulation must be endorsed where succeeding reflections must be retained. The implementation of telepharmacy systems is rapidly expanding due to the increasing affordability of videoconferencing technology and the increasing capability of the pharmacist to securely access electronic patient health records and perform traditional pharmacy practice activities remotely via the Internet. The number of scientifically-rigorous evaluations of telepharmacy has not kept pace with the rate of telepharmacy adoption.There must have been a certificate scheme according to the area of practice.Tele-pharmacy will be a great boon for a country like India with very huge population, where people from remote areas cannot reach upto a retail pharmacy, can order and buy drugs through online pharmacy.